2015
DOI: 10.1109/tfuzz.2014.2348017
|View full text |Cite
|
Sign up to set email alerts
|

Observer-Based Adaptive Fuzzy Tracking Control of MIMO Stochastic Nonlinear Systems With Unknown Control Directions and Unknown Dead Zones

Abstract: In this paper, an adaptive fuzzy backstepping output-feedback tracking control approach is proposed for a class of multi-input and multi-output (MIMO) stochastic nonlinear systems. The MIMO stochastic nonlinear systems under study are assumed to possess unstructured uncertainties, unknown dead-zones and unknown control directions. By using a linear state transformation, the unknown control coefficients and the unknown slopes characteristic of the dead-zones are lumped together and the original system is transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
213
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(213 citation statements)
references
References 41 publications
0
213
0
Order By: Relevance
“…Before introducing our control design method, let us first recall the approximation property of the NNs [11][12][13][14][36][37][38][39][40][41][42][43][44][45] . The NNs take the form of W T σ ( ξ ) where W ∈ R ×m is called weight matrix, with being the number of NN nodes; and σ (ξ ) ∈ R is a vector valued function defined in R , with ξ ∈ R q being the NN input vector.…”
Section: Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Before introducing our control design method, let us first recall the approximation property of the NNs [11][12][13][14][36][37][38][39][40][41][42][43][44][45] . The NNs take the form of W T σ ( ξ ) where W ∈ R ×m is called weight matrix, with being the number of NN nodes; and σ (ξ ) ∈ R is a vector valued function defined in R , with ξ ∈ R q being the NN input vector.…”
Section: Neural Networkmentioning
confidence: 99%
“…In [10] , with the consideration of controllability constraints arising due to underactuation, a nonlinear cooperative path following controller is developed, and that is suitable for both unidirectional and bidirectional communication links. However, a key feature of the aforementioned results [3,[8][9][10] is that the cooperative path following controllers are designed based on a backstepping technique [11][12][13] . The backstepping based cooperative path following controller has an obvious drawback.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes include epidemic spreading [5] and traffic flow [6]. Such processes have potential applications in the control of stochastic systems [7][8][9][10]. It has been demonstrated that the structural properties of networks play an important role in determining the dynamical features of these processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…This condition was reformulated into LMI. [28,29,30,31,32,33,34,35], which can be efficiently solved by using various convex optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%